Factors Related to the Risk of Falls in Patients with Osteoarthritis - Sinwisarn, Narumon; Palanupat, Thippawan; Yokseng, Jaruwan (Journal of The Royal Thai Army Nurses, 2024)
This research is a retrospective study examining factors related to the risk of falls in patients with osteoarthritis at the outpatient clinic of Thasala Hospital between January 2021 and December 2023. Adults and older individuals, 146 participants, were recruited for the study. Data was collected using personal information, evaluation and screening form for osteoarthritis and the fall risk assessment form for Thai elderly living in the community (Thai FRAT). The overall reliability for the entire set (r) was equal to 1.00. Data were analyzed using descriptive statistics, Chi-square relationship analysis, and binary logistic regression analysis. The results indicated that significant Factors associated with the risk of falls were found to be age, occupation, congenital disease, and knee joint pain with joint stiffness of less than 30 minutes. Factors predicting the risk of falls in patients with osteoarthritis include age, occupation, and knee joint pain with joint stiffness for less than 30 minutes with statistical significance (P<.05). Based on the findings of this study, nurses can use the research results to develop activities or programs to prevent falls in patients with osteoarthritis in both hospitals and communities.